HAEMATOLOGY PRACTICAL MANUAL FOR UNDERGRADUATES - Mei I Lai (Penerbit UTHM, 2017)
This book is intended to serve as a practical aid for students and an attempt to present haematology and transfucion medicine in a concise and simplified manner where areas of importance are highlighted. It is not aimed to replace for coverage of haematology available in text books but intended to assist students in understanding the laboratory aspects of haematology better. The reader should not expect to find comprehensive discussions of the topic dealt herein but importance of each laboratory test is highlighted including its practical aspects. The laboratory diagnosis of disorders in relation to red cell, white cell, haemostasis and aspects of transfusion medicine are discussed in a practical approach. Case studies form part of the integral approach to understand haematological diseases. This book is a ‘must’ for the desk of a students in laboratory aspects of haematology.